Endophytic fungi associated with Ziziphus species and new records from mountainous area of Oman (Biodiversitas Journal of Biological Diversity, 2016)
El-Nagerabi SAF, Elshafie AE, AlKhanjari SS. 2013. Endophytic fungi associated with Ziziphus species from mountainous area of Oman and new records. Biodiversitas 14: 10-16. Ziziphus species of the family Rhamnaceae grow extensively in arid and semi-arid regions. It is possible that the endophytic fungi associated with this plant might enhance the host resistance to the environmental impacts. The endophytic fungal population inhabiting the healthy leaves of Z. spina-christi and Z. hajanensis plants were determined from April 2008 to October 2011. The endophytic fungal communities varied between the two species, and 45 fungal species, 18 sterile mycelia and 12 yeasts were isolated from Z. spina-christi, whereas 35 fungi, 11 sterile mycelia and 5 yeasts were recovered from Z. hajanensis indicating tissue and species-specificity and without any seasonal variation among the endophytes. These endophytes are new to Ziziphus plants and 45 species are new to the mycoflora of Oman, whereas 27 species are new to Arabian Peninsula. The genus Alternaria was the most prevalent (19-81%) followed by Aspergillus (19-78%), Rhizopus stolonifer (78%), Mycelia sterilia (69%), yeasts (47%), Cladosporium (11-56%), Drechslera (14-53%), Curvularia (8-50%), Fusarium (6-33%), Ulocladium (41-31%), Penicillium (3-22%), Alysidium resinae (11%), Trichocladium (6-11%), Anguillospora longissima, Bactrodesmium rahmii, Catenularia (8%), Helminthosporium sorghi (7%), Dendryphiella infuscans (6%), Hansfordia biophila (3-6%), Arthrinium, Dissophora, and Phoma sorghina (3%). The recovery of many fungal isolates, morphologically various sterile mycelia and yeasts suggests the high biodiversity of the endophytes invading these plants with strong evidence for future isolation of numerous fungal species through adopting more advanced molecular and DNA identification methods.